Probing internal gradients dependence in sandstones with multi-dimensional NMR - Xiao, Lizhi; Liu, Huabing; Deng, Feng; Zhang, Zongfu; An, Tianlin; Zong, Fangrong; Anferov, Vladimir; Anferova, Sofia (Microporous and mesoporous materials, 2013)
[Display omitted] •Gin dependence on heterogeneity of sandstone structure is quantitatively studied.•3D pulse sequence is designed to encode T1, Gin, and T2 in respective windows.•3D data is processed with a designed fast three-dimensional inversion algorithm.•Dependence of internal gradients on field strength is nearly unity.•Gin in different pores at different B0 is an indicator of structural heterogeneity. Multi-dimensional NMR experiments at two magnetic field strengths (2 and 23MHz) are presented in this paper to study the dependence of effective internal gradients in water-saturated sandstone plugs. Special pulse sequence is designed to encode longitudinal relaxation time T1, internal gradient Gin and transverse relaxation time T2 in respective windows. Experimental three-dimensional data are processed with a fast 3D inversion algorithm. Within this one-shot experiment, the three-dimensional distribution function T1-Gin-T2 and projected one- and two-dimensional distributions monitor internal gradients through diffusion in pores and reveal how effective internal gradients scale with magnetic field. Contrasts in behavior of pore size components between the two field strengths, such as T1/T2 ratio increase in T2–T1 maps and signal up-shift in T1-Gin and T2-Gin maps, are associated with variations in effective internal gradients in porous media, so potentially indicating the physical dependence of internal gradients on static field strengths and on heterogeneity of the sandstone matrix.